The Establishment of Softskills Through Progressive Islamic Education - Muthoifin Muthoifin (Prosiding University Research Colloquium, 2022)
The purpose of this study was to determine the formation of students' soft skills through the implementation of Advanced Islamic Education. This type of research is a qualitative descriptive field. Data collection methods used include interviews and research methods. The research was conducted with a psychological approach. Furthermore, the descriptive data analysis method uses the inductive method. The object of research is Muhammadiyah Middle School Al-Kautsar PK Kartasura. The results of this study indicate that Advanced Islamic Education has a good impact and supports the formation of soft skills in students in schools through several aspects, including the learning process, school culture, and extracurricular activities. The soft skills formed include religious, disciplined, independent, cooperative, critical, and creative thinking processes, responsibility, leadership, problem-solving, creativity, and tolerance. Supporting factors in implementing the implementation of advanced Islamic education in forming soft skills include the leadership of the principal as a good role model, active communication and collaboration from all school stakeholders, high enthusiasm and commitment from all school stakeholders, adequate facilities and infrastructure, and qualified educators and staff of employees in their respective professional fields. Inhibiting factors in the implementation of advanced Islamic education in forming soft skills include the limited quantity of educators in implementing the program, students who do not obey school rules, lack parental attention and supervision with intensive activity, the rate of development of technology and information is not balanced with the ability of students to filter out positive and negative information.